System quality, information quality, satisfaction and acceptance of online learning platform among college students in the context of online learning and blended learning - Li, Xiaoxia; Zhu, Wanxia (Frontiers in Psychology, 2022)
The paper was based on the User Satisfaction and Technology Acceptance Integration Theory (USATA). The authors analyzed the factors that affect college students' acceptance and satisfaction of online learning platform, as well as the differences in the relationship between various factors in blended learning scenario and online learning scenario. The results showed that the quality of online learning platform and information quality affect user satisfaction, and satisfaction affects usefulness and ease of use, and then affect attitude and intention. The comparison between the two groups showed that there were significant differences in the impact of information quality on information satisfaction and the impact of perceived usefulness on usage intention. In the online learning scenario, the endogenous latent variables of the model had higher explanatory power, which indicates that learners are more dependent on the quality and relevant characteristics of the learning platform in the online learning scenario.